Diversity, Abundance, and Some Characteristics of Bacteria Isolated from Earth Material Consumed by Wild Animals at Kudurs in the Sikhote-Alin Mountains, Russia. (7th December 2020) - Lebedeva, Elena; Panichev, Alexander; Kharitonova, Natalya; Kholodov, Aleksei; Golokhvast, Kirill
Abstract : In this work, geochemical and microbiological studies were performed at kudurs in the southeastern part of the Sikhote-Alin mountain range and in the Sikhote-Alin Nature Reserve located in Primorsky Krai, Russia. It was found that the earth material eaten by wild animals in both sites is represented by clay-zeolite tuffs of dacite-rhyolite composition. In the earth material, Na is predominant in bioavailable macronutrients and Zn, light lanthanides, and Y in trace elements. Microbiological studies of geophagic earths revealed a wide range of heterotrophic and autotrophic aerobes and anaerobes involved in the conversion of carbon, nitrogen, and sulfur. Iron- and manganese-oxidizing bacteria and silicate bacteria were identified as well. The isolated pure cultures of heterotrophic bacteria were represented mainly by Gram-positive spore-forming large rods of Bacillus sp. and Gram-negative heterotrophic aerobic and facultative anaerobic microorganisms Burkholderia sp. and Microvirgula aerodenitrificans, which oxidize iron and reduce sulfate. The ability of the bacteria M. aerodenitrificans to reduce sulfates is shown for the first time. According to the literature, the isolated microorganisms are able to actively extract rare earth elements from earth materials, transforming them from the bioinert state to a state accessible to herbivorous mammals.